Queer coding in the Disney renaissance: locating queerness in Disney animated musicals and their remakes - Cowling, Ollie (2024)
This project concerns Beauty and the Beast (1991), Aladdin (1992), and The Lion King (1994) and their live action remakes. Each of the original films was released during the so- called Disney Renaissance, a period during which Disney saw a return to commercial success. Each of the films has become notable for the presence of queer coding. This project establishes that there are characters, Jafar and Scar who have queer theories based on stereotypes while there are also others who rely on details of the plot. The original versions each received more positive reviews than their remakes and this project discusses whether changes to queer coded characters have impacted this. I focus on Disney's acknowledgement of the importance of queer representation. Ultimately concluding that while we, as the audience, are entitled to interpret characters in any way we like Disney, because they know the importance of queer representation, should provide more openly queer characters.